201k views
4 votes
What is the sum of the geometric sequence -1, 6, -36, ....if there are 7 terms.

A) -39,991
B) -6,665
C) 6,665
D) 39,991

User Mbochynski
by
4.7k points

2 Answers

4 votes

Answer:

A) - 39,991

Explanation:

Sum of geometric sequence formula is


S = a((1 -r^n)/(1-r) )\\a=-1, r=6/(-1)=-6, n=7\\\\S = -1((1 -(-6)^7)/(1-(-6)) )= -(279937)/(7) = -39991

User ChaturaM
by
4.9k points
1 vote

Answer:

The correct answer option is A) -39,991.

Explanation:

We know that the sum of the geometric sequence is given by the formula:


S _ n = \frac { a _ 1 ( 1 - r ^ n ) } { 1 - r }

where
a_1 is the first term,
r is the common ratio and
n is the number of terms.

Here,


a_1 = -1


r = -6


n=7

Substituting these values in the above formula to get:


S _ 7 = \frac { -1 ( 1 - (-6) ^ 7 ) } { 1 - (-6) }

S_n = -39,991

User Fengelhardt
by
4.7k points